UMP, Communitising Science and Technology to Enhance The Quality of Stem Education - Rohana, Hamzah; Shamsul, Harbi (2018)
Pekan, 24-25 July 2018 - Universiti Malaysia Pahang (UMP) is a technological university with niche area in engineering. As a university focusing on science and technology, UMP has organized a workshop called “Menyemai Cinta Ilmu Sains dan Teknologi”. The objective of this workshop is to create a platform for knowledge sharing between UMP experts and educators aiming at improving teaching and learning techniques for these subjects; Science, Technology, and Mathematics. The organizing of this workshop is in line with one of UMP's sustainability goals which is to ensure the sustainability of talents available in UMP can be exploited by the local community and at the same time to improve current practice in teaching of Science and Mathematics in secondary school.